Constraints on jet quenching in p-Pb collisions at √sNN=5.02 TeV measured by the event-activity dependence of semi-inclusive hadron-jet distributions - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Borissov, Alexander; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; Ohlson, Alice; et al. (Physics letters, 2018)
The ALICE Collaboration reports the measurement of semi-inclusive distributions of charged-particle jets recoiling from a high-transverse momentum trigger hadron in p-Pb collisions at sNN=5.02 TeV. Jets are reconstructed from charged-particle tracks using the anti-kT algorithm with resolution parameter R=0.2 and 0.4. A data-driven statistical approach is used to correct the uncorrelated background jet yield. Recoil jet distributions are reported for jet transverse momentum 15<pT,jetch<50GeV/c and are compared in various intervals of p-Pb event activity, based on charged-particle multiplicity and zero-degree neutral energy in the forward (Pb-going) direction. The semi-inclusive observable is self-normalized and such comparisons do not require the interpretation of p-Pb event activity in terms of collision geometry, in contrast to inclusive jet observables. These measurements provide new constraints on the magnitude of jet quenching in small systems at the LHC. In p-Pb collisions with high event activity, the average medium-induced out-of-cone energy transport for jets with R=0.4 and 15<pT,jetch<50GeV/c is measured to be less than 0.4  GeV/c at 90% confidence, which is over an order of magnitude smaller than a similar measurement for central Pb-Pb collisions at sNN=2.76TeV. Comparison is made to theoretical calculations of jet quenching in small systems, and to inclusive jet measurements in p-Pb collisions selected by event activity at the LHC and in d-Au collisions at RHIC.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Borissov, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, M.K. Köhler, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 04.07.2019